Representation of gender and feminist values in the television series the Marvelous Mrs. Maisel (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2025)
This paper is framed within the context of gender studies that examine the representation of women in audiovisual media and focuses specifically on a television series as a case study. The main objective is to analyse the representation of the female protagonists of the series The Marvelous Mrs. Maisel (Prime Video, 2017-2023) from a gender perspective. To achieve this, a textual analysis based on the identification and description of the traits that characterise the female protagonists, Miriam Maisel and Susie Myerson, is applied. Through a phenomenological approach, three dimensions are studied: physical, psychological and social. The second objective is to evaluate this representation in terms of the principles of different waves of the feminist movement and the possible presence of sexist stereotypes. The results lead to the conclusion that the series proposes a revision of the 1950s by presenting women who challenge the patriarchy of the time through their artistic and professional activity. The research concludes that, although there are some conventional physical representations of beauty and youth, the female characters exhibit a psychological and social depth that transcends classic stereotypes. The series aligns itself with contemporary feminist values, especially those of the second and fourth waves, by denouncing gender discrimination and advocating for equality.
Keywords: Television series; digital platforms; gender studies; feminism; media analysis